Research Problem Field of Alcoholization among the indigenous population of the Republic of Tuva - Vangorodskaya, Svetlana A. (The New Research of Tuva, 2025)
The article presents an analysis of 525 scholarly publications in Russian (research articles, dissertations, etc.), available in the Scientific Electronic Library, published between 1999 and 2025. These were selected using search queries that reflect various aspects of alcohol consumption among the indigenous population of Tuva — the Tuvans.The author examined the research problem field concerning the alcoholization of the indigenous population and identified five main groups of determinants responsible for the high levels of alcohol consumption in the Republic of Tuva: ethnocultural, natural-climatic, socio-economic, political, constitutionally determined, and neuropsychological.The group of ethnocultural determinants includes centuries-old traditions of using alcohol as a psychotropic substance; cultural norms of consumption; traditional gender roles; the institution of the family; intergenerational ties, and others. The primary socio-economic factors cited are low standard of living and high unemployment rates, low per capita incomes, the development of the shadow sector of the alcohol market, and the decline in the effectiveness of the primary prevention system for alcoholism.The study revealed a significant role of political factors (instability in the domestic political situation) and natural-climatic factors (harsh climatic conditions) in shaping alcohol consumption among the indigenous population of Tuva.Constitutionally determined and neuropsychological characteristics of the indigenous peoples of Siberia are highlighted separately: right-hemisphere dominance, which predisposes Tuvans to the accelerated development of alcohol dependence; ethnic features of the emotional sphere of Tuvans and the specifics of their emotional responses; a deficiency in the aldehyde dehydrogenase isoenzyme in their blood; high rates of progressive alcoholism combined with reduced population resilience to alcohol; and the predominance of submissive motivation in the structure of alcohol-related motivations.The author concludes that there is a need to develop a set of measures that, on the one hand, consider the pronounced ethnocultural specificity of the Republic of Tuva, and on the other hand, utilize the positive experience of Russian regions and foreign countries in reducing alcohol consumption and mitigating the associated risks.
Keywords: alcohol consumption; determinant of alcohol use; demographic situation; demographic indicator; Republic of Tuva; indigenous population; Tuvans